Post myocardial infarction ionic remodelling promotes repolarisation dispersions and abnormalities in acute and chronic stages. (24th May 2021) - Zhou, X; Wang, Z; Tomek, J; Wang, L; Rodriguez, B
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Wellcome Trust Background: Sudden cardiac death after a myocardial infarction (MI) was reported in both the acute stage and the chronic stage with the development of heart failure (HF). Around 50% of these deaths were due to ventricular tachyarrhythmia which is related to the temporal dispersion of repolarisation caused by the post-MI remodelling of ionic currents. While variable extent of ionic current changes was observed in multiple animal species in different post-MI phases, the proarrhythmic effects of such remodelling in post infarction human hearts is not fully explored. Purpose: The goal of this study is to explore the proarrhythmic effects of post-MI ionic remodelling in human ventricular myocyte models of electrophysiology for both the acute and the chronic stages. Methods: The ToR-ORd human ventricular cellular model was used as the baseline model, and a new formulation of the calcium activated potassium current was implemented. We constructed and calibrated a population of 253 human ventricular cell models (POM) to represent electrophysiological variability of normal zone (NZ) myocytes. For the acute phase, three types of border zone (BZ) remodelling (Acute BZ1-3) were introduced based on dog experimental data collected within one week after infarction. For the chronic phase with the development of HF, BZ (Chronic BZ) and one type of remote zone (RZ) remodelling (Chronic RZ1) were introduced based on minipig data collected 5 months post-MI. Another type of RZ remodelling (Chronic RZ2) was introduced based on experimental data from failing human hearts. The cellular models were paced at cycle lengths of 1000ms, 500ms, 400ms and 300ms for 500 beats before the analysis of repolarization abnormalities. Results: For both the acute and the chronic stages post-MI, the extent of repolarisation dispersion between BZ and the corresponding NZ and RZ varied from 2ms up to 120ms, and largely depended on the level of potassium current remodelling. A weaker calcium transient was always observed in the BZ. Early after depolarisations (EADs) and repolarisation failure (RF) were observed in the chronic stages, caused by the reactivation of L-type calcium current due to the augmentation of late sodium current and the inhibition of hERG current. Beat-to-beat repolarization alternans was observed in both the acute and the chronic stages, with the key ionic mechanisms being the inhibition of SERCA activity and the slower calcium release due to enhanced CaMKII. Conclusions: Post-MI ionic remodelling of the acute and chronic stages can cause a substantial dispersion of repolarisation in human hearts by inducing the prolongation of action potential durations, EADs, RFs, and alternans, providing substrates for the generation and maintenance of lethal reentrant waves.